The beauty of the beast: Suggestions to curb the excesses of dog breeding and restore animal welfare - Invited review - C Diederich (Veterinární Medicína)
Dog. Specifically created to save its master's life. - (The dog is the ideal) Friend of man, (because it is his devoted slave) (source: Gustave Flaubert, Dictionnaire des Idées Reçues). But is man the best friend of the dog? This question is legitimate when we consider living situations to which modern domestic dogs are exposed. They often do not satisfy basic animal needs. In this narrative review, the author revisits the history of the dog's presence alongside humans, in the light of current knowledge. The modern dog (breed standards and their interests in canine research) and its breeding strategy, including extreme breeding, will then be given particular attention. Dysfunctional human psychological processes will be explored to make it possible to grasp why the breeding of the modern dog is undergoing such a transformation. Finally, based on these factual and conceptual insights, suggestions to improve canine welfare will be proposed. To be effective, all these must be assessed against real-world conditions.